Microsurgical Anatomy of the Cavernous Sinus: Anatomical Review and Multimodal Management.: https://doi.org/10.59156/revista.v37i03.305 - Cespedes, Jairo; Muftah Lahirish, Issa Ali (Revista Argentina de Neurocirugía, 2023)
Background: Cavernous sinus surgery was long considered unfeasible (not accessible to humans) (5.31) due to the risk of bleeding or injury to critical neurovascular structures, such as the ICA, oculomotor, trochlear and abducens nerves (5.31). Since then, numerous studies have contributed to understanding the microsurgical anatomy of the cavernous sinus. In 1965, Parkinson (25) performed the first approach to the cavernous sinus for the treatment of carotid-cavernous fistula. This was the beginning of the modern era in cavernous sinus surgery and opens the door to many publications detailing surgical approaches to various injuries in and around the cavernous sinus. Together with the development and improvement of neuroimaging and microsurgical anatomy, they allowed successful access to the cavernous sinus. Our goal is to present a state-of-the-art narrative review of cavernous sinus microsurgical anatomy and interdisciplinary management. To achieve this purpose, cadaveric dissection of 2 heads (four cavernous sinuses) was performed, reflected in 2 surgical cases, in addition to an exhaustive literature review that guides the multimodal management of tumors found within or around the cavernous sinus. Objective: The aim of this study is to describe the surgical anatomy of the cavernous sinus through cadaveric dissections and its microsurgical application. Methods: 4 human cadaveric cavernous sinuses fixed in formalin were studied, the arteries and veins were injected with colored silicone, the images were taken with a 24.2-megapixel Nikon 3400 professional DSLR camera. Results: The cavernous sinus is a dural compartment that contains critical neurovascular structures, whose dissection must be performed carefully and neatly due to the imminent risk of injury to them, so lesions confined, for example, to the lateral wall (clinical case 2 ) have a higher probability of total removal and therefore a better prognosis, but not lesions that invade the cavernous sinus (clinical case 1) itself, where the probability of total removal decreases and the risk of neurovascular injury increases. Conclusions: Precise knowledge of the microsurgical anatomy of the cavernous sinus and multimodal management are crucial in the management and prognosis of the patient.